Laboratory biomarkers for multiple sclerosis and their role in clinical practice - Navickaitë, I.; Žemgulytė, G.; Balnytė, R. (Neurologijos seminarai, 2023)
Multiple sclerosis (MS) is a chronic disease of the central nervous system (CNS) most commonly diagnosed in young adults. In recent decades, new treatments have emerged that have radically changed the prognosis and quality of life of these patients. However, this has also raised new challenges in predicting the course and activity of the disease before the development of new neurological deficits that aggravate the disability and in prescribing the most appropriate disease-modifying therapy for the individual patient in a timely manner. One of the possible solutions that could help answer these questions is the use of laboratory biomarkers in MS. In addition to the oligoclonal bands (OGB) and the immunoglobulin G index, which are already well known and clinically useful laboratory tests, other biomarkers have been discovered that can assess the inflammatory and neurodegenerative processes occurring in the CNS. Kappa free light chains and K-index have been identified as new potential diagnostic biomarkers for MS, with similar sensitivity and specificity to OGB. Some biomarkers have also shown the ability to differentiate a clinically isolated syndrome from MS and to identify the clinical course of MS. The concentration of chitinase-3-like protein in the cerebrospinal fluid is currently the only biomarker that can help distinguish MS from a clinically isolated syndrome. Levels of glial fibrillary acidic protein in cerebrospinal fluid and blood serum can help distinguish primary progressive MS from the relapsing-remitting course of this disease. Serum neurofilament light chain levels are considered the most useful biomarker for monitoring disease activity and treatment efficiency. This article discusses the most promising biomarkers for MS diagnosis, disease activity, and treatment response.